ANALISIS PENGGUNAAN KANDOUSHI OUTOU DALAM KOMIK NARUTO VOLUME I - gamis kurniawan; Hendri Zalman (Universitas Negeri Padang, 2021)
Kandoushi outou is a kandoushi that expresses answers from others. If you do not understand kandoushi outou then it can cause problems, one of which is not understand what the intention of others, then one of the effects can cause miscommunication or the speaker's intentions are not conveyed to others. This research aims to describe the use and function of kandoushi outou in Naruto comics volume I. The type of this research is qualitative research with descriptive methods. The data source of this study is Naruto comic volume I. In this study found 31 kandoushi data, namely 4 imperative sentence, 1 wish sentence, 4 Interrogative sentence and 22 Declarative sentence. The conclusion of this study is the things that affect outou kandoushi arise based on the context or situation of each of these conversations. This outou kandaoushi is not bound by the standard rules of language.